Аntagonistic effect of a mixture of bioactive cow's colostrum fragments on pathogenic microorganisms - Zayarnyuk, Anna (My University, 2018)
Obtained results demonstrate the direct inhibitory effect of the mixture of bioactive fragments of colostrum on the cells of microorganisms, which leads to inhibition of their growth and development in vitro. It suppresses the development of due to the high acidity and due to the content of lysozyme, which dissolves the membranes of microorganisms. Thus, this study confirms the prospect forfurther study of the interaction of biologically active fragments with macroorganism under in vivo conditions, the creation of antimicrobial and prophylactic protein preparations of natural origin on the basis of colostrum, to which there is no resistance that will not cause allergic reactions, and will be safe even for children.

Отримані результати досліджень демонструють пряму інгібувальну дію суміші біоактивних фрагментів молозива на клітини мікроорганізмів, що призводить до пригнічення їх росту та розвитку in vitro. Розвиток патогенних мікроорганізмів пригнічується завдяки високій кислотності і завдяки вмісту лізоциму, який розчиняє мембрани мікроорганізмів. Таким чином, дане дослідження підтверджує перспективу подальшого вивчення взаємодії біологічно активних фрагментів з макроорганізмом в умовах in vivo, створення протимікробних і профілактичних білкових препаратів природного походження на основі молозива, до яких не існує резистентності, яка не викликатиме алергічних реакцій, і буде безпечною навіть для дітей.
Keywords: colostrum; mixture of bioactive fragments of colostrum; pathogenic microorganisms; immunity; молозиво; суміш біоактивних фрагментів молозива; патогенні мікроорганізми; імунітет; кафедра біотехнології і мікробіології